Immune dysregulation increases the incidence of delayed‐type drug hypersensitivity reactions. Issue 4 (23rd December 2019) - Naisbitt, Dean J.; Olsson‐Brown, Anna; Gibson, Andrew; Meng, Xiaoli; Ogese, Monday O.; Tailor, Arun; Thomson, Paul
Abstract: Delayed‐type, T cell–mediated, drug hypersensitivity reactions are a serious unwanted manifestation of drug exposure that develops in a small percentage of the human population. Drugs and drug metabolites are known to interact directly and indirectly (through irreversible protein binding and processing to the derived adducts) with HLA proteins that present the drug‐peptide complex to T cells. Multiple forms of drug hypersensitivity are strongly linked to expression of a single HLA allele, and there is increasing evidence that drugs and peptides interact selectively with the protein encoded by the HLA allele. Despite this, many individuals expressing HLA risk alleles do not develop hypersensitivity when exposed to culprit drugs suggesting a nonlinear, multifactorial relationship in which HLA risk alleles are one factor. This has prompted a search for additional susceptibility factors. Herein, we argue that immune regulatory pathways are one key determinant of susceptibility. As expression and activity of these pathways are influenced by disease, environmental and patient factors, it is currently impossible to predict whether drug exposure will result in a health benefit, hypersensitivity or both. Thus, a concerted effort is required to investigate how immune dysregulation influences susceptibility towards drug hypersensitivity.